The Territorial Dimension of the European Social Fund A Local Approach for Local Jobs? - Martinez-Fernandez, Cristina (OECD Publishing, 2011)
The European Union Treaty of Lisbon brought a new dimension to cohesion - the territorial dimension, which has become one of the most frequently discussed aspects for achieving cohesion and, at the same time, one of the challenges for EU policies. The 'territorial dimension' determines many socio-economic problems and presents challenges for the European Social Fund (ESF), which has to enhance its flexibility and highlight the capacity and needs of specific territories at national, regional and local levels at the programming and implementation stages. While our understanding of the national and regional levels has advanced, the dynamics with the local level need further consideration, chiefly in the context of Europe 2020 strategy, and regarding the territorial dimension of the European Social Fund and mechanisms of territorialisation. This paper discusses the conceptualisation of territoriality and the different levels of applicability in regional development approaches. The paper draws on OECD and other organisations research and analysis; particularly the work of the OECD Local Economic and Employment Development Programme (LEED). The paper argues that the local level is emerging as the key spatial dimension where EU development instruments apply and therefore a systemic local approach may be needed when designing national and regional cohesion policies and instruments. The paper is divided into 5 sections discussing: 1) The importance of an integrated spatial approach to development; 2) The success of the local approach to development: complexity, integration and the policy mix; 3) Integrating territorial mechanisms for job creation, employability and inclusive growth; 4) Fostering education policies for qualification and skills rich ecosystems; and 5) The way forward
Keywords: Urban, Rural and Regional Development; Industry and Services